(untitled) - Kamen, Edward W. (New York, 1987)
Kamen's book contains all the mathematics and technical concepts that other communications texts contain but the author presents this information is such a manner that it is more readily absorbed.
Keywords: Signal theory (Telecommunication),Lý thuyết tín hiệu (Viễn thông)